Implementasi Perancangan User Experience Code Maniac dengan Pendekatan Human-Centered Design (HCD) - Makhdoum Tosinmim; Retno Indah Rokhmawati; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Code Maniac is a gamification-based programming learning platform built by the development team of the Faculty of Computer Science Universitas Brawijaya (FILKOM UB), requires interface improvements to find refined design according to user needs and goals. This study aims to evaluate and produce interface design solutions using the Human-Centered Design (HCD) method based on the problems obtained. In addition, the usability level of the early design and the repair solution was also carried out. The usability level assessed includes three aspects, namely effectiveness, efficiency, and satisfaction. Initial design testing was carried out on eleven participants to run test scenarios and an emoticon table to find out what users felt. Meanwhile, the solution design test was conducted on eight participants using the USE Questionnaire to measure satisfaction. The design of the solution design improvement is made in the form of an interactive. The final results of this study get improvement design show an increase in all aspects of the test, namely the effectiveness aspect to 100%, the efficiency aspect with a Time-Based Efficiency (TBE) value of 0,064 goals/sec and an Overall Relative Efficiency (ORE) value of 100% which indicates that the solution design improvement the solution design has a better usability rate than the old design. The satisfaction aspect gets an average percentage value of 87,4%, Code Maniac is included in the â€œVery Eligibleâ€ category..